Ultrasensitive amplicon barcoding for next-generation sequencing facilitating sequence error and amplification-bias correction - Ahmed, I; Tucci, FA; Aflalo, A; Smith, KGC; Bashford-Rogers, R (Nature Research, 2020)
The ability to accurately characterize DNA variant proportions using PCR amplification is key to many genetic studies, including studying tumor heterogeneity, 16S microbiome, viral and immune receptor sequencing. We develop a novel generalizable ultrasensitive amplicon barcoding approach that significantly reduces the inflation/deflation of DNA variant proportions due to PCR amplification biases and sequencing errors. This method was applied to immune receptor sequencing, where it significantly improves the quality and estimation of diversity of the resulting library.